Clinical profile of Indonesian children with anterior segment dysgenesis as a contributor for childhood blindness - Dian Estu Yulia; Febianza Mawaddah Putri; Diajeng Ayesha Soeharto (Elsevier, 2023)
Background: Anterior segment dysgenesis (ASD) is an ocular malformation that can lead to childhood blindness. Although ASD prevalence is rare, it is potentially devastating for children and caretakers. We aim to report the clinical features of ASD patients in a tertiary referral center in Indonesia. Methods: We conducted a retrospective review of medical records of ASD patients in the Pediatric Ophthalmology clinic in Cipto Mangunkusumo National Central Public Hospital, Jakarta, Indonesia between January 1, 2018, and December 31, 2021. Results: A total of 172 eyes of 107 children with ASD were included in this study. Most of the patients were male, aged 3.4 years ±5.0 SD at first examination, 67.3% patients came from outside Jakarta, and 75.6% of eyes had bilateral ASD. Most common clinical manifestations was congenital corneal opacities (CCO), microcornea, and congenital glaucoma. The most common visual acuity (VA) was fixation and following light/object. Intraocular pressure (IOP) increased in 41% eyes. The most common surgery performed was glaucoma surgery, which was performed in 6.4% of eyes in the study. Conclusion: ASD has a devastating impact on children's VA, along with its poor prognosis despite surgery thus contributes largely to childhood blindness. ASD detection and management is highly challenging in children, and increased awareness on ASD is pivotal in earlier referral and treatment of ASD.